Effectiveness of immunocastration in adult boars - Agudelo-Trujillo J.; Estrada-Pineda J.; Guzmán-González P. (7th International Symposium on the Mediterranean Pig, 2012)
Immunocastration (IC) of pigs during their finishing stage avoids the traumatic castration surgery (Q) still practiced in many countries to prevent boar taint in pork. We have not found reports on IC of culled adult boars. In this study we evaluated boar taint, spermatogenesis, and weight loss of adult boars after castration by IC versus Q. A total of 21 boars were used (age: 29 months). The IC boars (n: 12) were injected with Innosure® (Pfizer Inc), and repeated four weeks later. The Q pigs (n: 9) were castrated when the IC were first injected. Both groups were monthly weighted and slaughtered five weeks after the second injection. Testes of IC slaughtered boars were sampled and compared with the Q group. Odor panels were conducted to test all carcasses and pork. The Q boars lost 0.172 kg BW/animal/day, while IC boars did not lose weight (P=0.016). None of the boars (IC or Q) resulted in tainted pork. The IC testes had lower spermatogenesis compared to Q. It is concluded that IC effectively prevented boar taint through testicle atrophy, and it also resulted in no weight loss after castration.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)